Antinociceptive, anti-inflammatory and antipyretic properties of the aqueous extract of Bauhinia purpurea leaves in experimental animals - Zakaria, Zainul Amiruddin; Loo, Yi Wen; Abdul Rahman, Nurul Izzah; Abdul Ayub, Abdul Halim; Sulaiman, Mohd Roslan; Gopalan, Hanan Kumar (S. Karger AG, 2007)
Objective: The present study was carried out to determine the antinociceptive, anti-inflammatory and antipyretic activities of the aqueous extract of Bauhinia purpurea leaves using animal models. Materials and Methods: The air-dried, powdered leaves (≈20 g) were soaked in distilled water (1:20; w/v) at room temperature for 72 h and the supernatant obtained was freeze-dried. The crude dried extract (≈2.4 g) was prepared in doses of 6.0, 30.0 and 60.0 mg/kg, and subjected to the respective antinociceptive (abdominal constriction, hot plate and formalin tests), anti-inflammatory (carrageenan-induced paw edema test) and antipyretic (brewer's yeast-induced pyrexia test) assays. Results:The results obtained indicate that the extract possessed significant (p < 0.05) antinociceptive, anti-inflammatory and antipyretic activities, which were not dependent on the doses of extract used. The highest concentration of extract was less effective as an anti-inflammatory and an antipyretic agent. Conclusion: This study showed that the aqueous extract of B. purpurea leaves possesses potential pharmacological activities that require further investigation and, thus, confirms the folklore use of the plant in the treatment of ailments associated with pain and inflammation.